Insulin Reciprocally Regulates Glucagon Secretion in Humans - Cooperberg, Benjamin A. (American Diabetes Association, 2010)
OBJECTIVE: We tested the hypothesis that an increase in insulin per se, i.e., in the absence of zinc, suppresses glucagon secretion during euglycemia and that a decrease in insulin per se stimulates glucagon secretion during hypoglycemia in humans. RESEARCH DESIGN AND METHODS: We measured plasma glucagon concentrations in patients with type 1 diabetes infused with the zinc-free insulin glulisine on three occasions. Glulisine was infused with clamped euglycemia (∼95 mg/dl [5.3 mmol/l]) from 0 to 60 min on all three occasions. Then, glulisine was discontinued with clamped euglycemia or with clamped hypoglycemia (∼55 mg/dl [3.0 mmol/l]) or continued with clamped hypoglycemia from 60 to 180 min. RESULTS: Plasma glucagon concentrations were suppressed by −13 ± 3, −9 ± 3, and −12 ± 2 pg/ml (−3.7 ± 0.9, −2.6 ± 0.9, and −3.4 ± 0.6 pmol/l), respectively, (all P < 0.01) during zinc-free hyperinsulinemic euglycemia over the first 60 min. Glucagon levels remained suppressed following a decrease in zinc-free insulin with euglycemia (−14 ± 3 pg/ml [−4.0 ± 0.9 pmol/l]) and during sustained hyperinsulinemia with hypoglycemia (−14 ± 2 pg/ml [−4.0 ± 0.6 pmol/l]) but increased to −3 ± 3 pg/ml (−0.9 ± 0.9 pmol/l) (P < 0.01) following a decrease in zinc-free insulin with hypoglycemia over the next 120 min. CONCLUSIONS: These data indicate that an increase in insulin per se suppresses glucagon secretion and a decrease in insulin per se, in concert with a low glucose concentration, stimulates glucagon secretion. Thus, they document that insulin is a β-cell secretory product that, in concert with glucose and among other signals, reciprocally regulates α-cell glucagon secretion in humans.